Risk of health morbidity for the uninsured: 10-year evidence from a large hospital center in Boston, Massachusetts. (18th August 2018) - Chen, Zhaoyi; Min, Jae; Bian, Jiang; Wang, Mo; Zhou, Le; Prosperi, Mattia
Abstract: Objective: To investigate the independent contribution of insurance status toward the risk of diagnosis of specific clinical comorbidities for individuals admitted to intensive care unit (ICU). Design: Retrospective analysis of secondary database. Setting: Ten years of public de-identified ICU electronic medical records from a large hospital in USA. Participants: Patients (18–65 years old) who had private insurance or no insurance were extracted from the database. Main outcome measures: Independent association of insurance status (uninsured vs. privately insured) with the risk of diagnosis of specific clinical comorbidities. Results: Among 14 268 (from 11 753 patients) admissions to ICU between 2001 and 2012, 96% of them were covered by private insurance. Patients with private insurance had higher proportion of females, married, White race, longer ICU stay and more procedures during stay, and fewer deaths. A lower CCI was observed in uninsured patients. At multivariable analysis, uninsured patients had higher odds of death and of admissions for accidental falls, substance or alcohol abuse. Conclusions: Patients with no insurance coverage were at higher risk of death and of admission for physical and substance-related injury. We did not observe a higher risk for acute life-threatening diseases such as myocardial infarction or kidney failure. The lower CCI observed in the uninsured may be explained by under diagnosis or voluntary withdrawal from coverage in the pre-Affordable Care Act era. Replication of findings is warranted in other populations, among those with government-subsidized insurance and in the procedure/prescription domains.